Changes in Tear Film and Ocular Surface after Phacoemulsification for Senile Cataract - Adila Anwar, M. Mumtaz Chaudhry, Samra Ahmed, Qurat ul Ain Malik, Misbah Naeem, Amna Mangrio, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the changes in “ocular surface” and “tear film” of patients who underwent phacoemulsification for senile cataract at Federal Government Polyclinic Hospital, Islamabad. Methodology: This study was conducted from 1-10-2022 to 31-12-2022. 66patients with senile cataract were selected for this study. After taking consent baseline features including age, gender, duration of cataract, was recorded were documented on the proforma. Preoperative and post-operative OSDI, TBUT, TMH and CFS at 1 and 4 weeks to assess changes in “ocular surface” and “tear film” were recorded. Data was analyzed by SPSS 21. Results: A total of 66eyes of 66 patients were made part of the study having a mean age of 65.32 ± 4.45 years. 77.3% of study participants were male while 22.7% were females. OSDI, TBUT, TMH and CFS were significantly effected (p-values of 0.000, 0.003, 0.000 and 0.000, respectively). No statistically significant difference was found in these parameters between male and female patients (p > 0.05). Overall frequency of patients who had OSDI ≥ 33, TBUT ≤ 10 seconds and TMH ≤ 0.3mm was 22% each while CFS was present in 19.7% of the patients. Conclusion: Phacoemulsification of senile cataract significantly effects the tear film and ocular surface, however, the change is a transient one. Key Words: Phacoemulsification, TBUT, Senile Cataract, CFS, OSDI.